2005
DOI: 10.1590/s1519-566x2005000600017
|View full text |Cite
|
Sign up to set email alerts
|

Ants as carriers of antibiotic-resistant bacteria in hospitals

Abstract: Neotropical Entomology 34(6): 999-1006 (2005) Formigas Como Agentes Carreadores de Bactérias Resistentes em Hospitais RESUMO -A presença de bactérias resistentes a antimicrobianos e carreadas por formigas isoladas em hospitais foi investigada em Campos dos Goytacazes, RJ. Três instituições de saúde foram visitadas nos períodos de 2001 a 2002 e amostras foram coletadas em áreas de cuidados médicos consideradas críticas baseando-se em critérios de maior risco para a aquisição de infecções por pacientes hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
44
1
40

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(91 citation statements)
references
References 30 publications
6
44
1
40
Order By: Relevance
“…As in the case of the CNS, this suggests that these insects may be responsible for carrying and distributing GNB bacteria both inside and outside the hospital environment. The 16.7% contamination rate of ants by such bacteria in the hospital was lower than Moreira et al (2005) found and the 66.7% found by Peçanha (2000). TC were found on two occasions in samples collected from the environment, hospital and laboratory.…”
Section: Resultscontrasting
confidence: 55%
See 3 more Smart Citations
“…As in the case of the CNS, this suggests that these insects may be responsible for carrying and distributing GNB bacteria both inside and outside the hospital environment. The 16.7% contamination rate of ants by such bacteria in the hospital was lower than Moreira et al (2005) found and the 66.7% found by Peçanha (2000). TC were found on two occasions in samples collected from the environment, hospital and laboratory.…”
Section: Resultscontrasting
confidence: 55%
“…Out of all the strains isolated from ants found in the hospital, 58.3% were CPS, a very high rate when compared with the 8.3% found by Peçanha (2000) and Moreira et al (2005). It is worth noting that both authors isolated only S. aureus.…”
Section: Resultsmentioning
confidence: 68%
See 2 more Smart Citations
“…Diferentes autores vêm alertando sobre o papel específi co de insetos no transporte de microrganismos associados a ambientes hospitalares e infecções nosocomiais (Fotedar et al 1991, Daniel et al 1994, Peçanha 2000, Fontana et al 2001. Entre os insetos, o papel das formigas nos hospitais vem sendo cada vez mais discutido (Fowler et al 1993, Bueno & Fowler 1994, Delabie et al 2002, Moreira et al 2005. Estima-se que existem 21.000 espécies de formigas no planeta, sendo que aproximadamente 12.500 já foram descritas, 3.000 no Brasil.…”
unclassified